Optimal size of government and economic growth in Malaysia: empirical evidence - Ahmad, Riayati; Othman, Norashida (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2014)
An increased integration of the world economy over the last few decades has led to growing interest in its effects on different aspects of national economies. One aspect that has drawn particular attention is the effect on government spending. However, the relation between government size and economic growth is ambiguous. There are persuasive arguments for both positive and negative impacts on economic growth. This paper aims to test long run relation between government size and economic growth. Specifically, it test whether there is an “inverted U" shape relationship between public spending and economic growth or not and to find the optimal level of government size in Malaysia. It is important to measure the optimal level of government size to ensure its play an efficient role in the economy. Using the autoregressive distributed lag (ARDL) bound testing approach, the result shows that government size in Malaysia is not exceed the optimal level. Based on the results of the study, an economic policy proposal may be that the share of public expenditure and the effectiveness of public expenditure programs should be increased to foster economic growth in Malaysia.